Anti-αvβ3 Antibodies in Chronic Immune Thrombocytopenic Purpura - Kosugi, Satoru; Tomiyama, Yoshiaki; Honda, Shigenori; Kashiwagi, Hirokazu; Shiraga, Masamichi; Tadokoro, Seiji; Kiyoi, Teruo; Kurata, Yoshiyuki; Matsuzawa, Yuji (Thrombosis and Haemostasis, 2001)
In chronic immune thrombocytopenic purpura (ITP), anti-GPIIb-IIIa (αIIbβ3) autoantibodies have been detected in serum and/or platelet-associated IgG (PAIgG) and considered as one of the major causes. We examined whether anti-αvβ3 antibodies might be present in ITP cases because of the similarity between αvβ3 and GPIIb-IIIa (αIIbβ3). Modified antigen capture ELISA (MACE) using human umbilical vein endothelial cells (HUVEC) showed the presence of serum anti-αvβ3 antibodies in 23 of 80 ITP patients (29%). Cross-adsorption studies between platelets and HUVEC demonstrated that most of anti-αvβ3 and anti-GPIIb-IIIa antibodies exclusively reacted with αvβ3 and GPIIb-IIIa, respectively. Platelet-associated anti-GPIIb-IIIa antibodies did not react with αvβ3, either. Interestingly, patients having anti-αvβ3 antibodies showed significantly lower platelet counts than negative patients. These results indicate the serum anti-αvβ3 antibodies are different ones from the classical anti-GPIIb-IIIa (αIIbβ3) antibodies and would provide a new insight into the pathophysiology of ITP as well as the autoantigenic epitopes on β3 integrins.
Keywords: ITP; autoantibody; β3 integrin; GPIIb-IIIa; αvβ3